Trend and Epidemiology of Tetanus in Nasarawa State, Nigeria: A Five Years Review - Hassan Ikrama Ibrahim; Bello Surajudeen Oyeleke; Odonye Caleb Eselema; Lawal Abdulmumuni; Audu Esther Solomon; Anazodo Michael Chidi (Masters Program in Public Health, 2023)
Background: Tetanus is a vaccine preventable, non-communicable disease known as lockjaw and characterized by muscle spasm. It is a forgotten disease in the developed world but remained an infection of public health importance in the developing countries. This study aimed to determine the trend in its epidemiology and outcome in Nasarawa state. Subjects and Method: A retrospective study using secondary data from the medical records of three selected health facilities, one each across the three senatorial zones of the state. All those who had tetanus were included while those with incomplete records, 5 were excluded. Data analysis was done using a statistical package for social sciences version 23. The dependent variable was the outcome of tetanus while the independent variables were incubation period, onset period, type of tetanus, risk factors, vaccination history, and manifestations of tetanus. Results: The subject consists of 53.8% males and single with age (Mean=15; SD=6.90). Four and 17 days were the shortest and longest incubation periods while one and six days were the shortest and longest onset periods respectively. A total of 24 (93.3%) patients had generalized tetanus. Nail puncture, road traffic accidents, and umbilical infection were the commonest sources of post-neonatal and neonatal tetanus in this study. Spasm is the commonest manifestation, present in 19 (73.1%) of the study population. This is closely followed by trismus in 57.7% of the cases. About half have a positive vaccination history. This study found case fatality of 7.7%. Conclusion: Generalized tetanus was the commonest type seen in this study, while nail puncture, road traffic accident and umbilical infection were the most common sources of infection. Although, more than half of the study subjects received immunization to prevent tetanus, the case fatality in this study was in one in twelve sufferers. Keywords: Epidemiology, review, tetanus, trend. Correspondence:Bello Surajudeen Oyeleke. Department of Paediatrics Dalhatu Araf Specialist Hospital. Shendam Road, PMB 07, Lafia, Nasarawa State. Email: surajudeenbello4@gmail.com. Mobile: +2347064641540.